Modification of nitrogen doped carbon for SILP catalyzed hydroformylation of ethylene. Issue 23 (22nd September 2017) - Weiß, Alexander; Giese, Matthias; Lijewski, Martin; Franke, Robert; Wasserscheid, Peter; Haumann, Marco
Abstract : Nitrogen-doped carbon is a new material for SILP catalysts that show improved performance as function of N-content and surface basicity. Abstract : We report the application of nitrogen doped carbon (NDC) materials as supports for the SILP catalyzed gas-phase hydroformylation of ethylene. The Rh–xantphos complex, dissolved in [EMIM][NTf2 ] and dispersed onto commercially available activated carbon yielded low activity. The incorporation of nitrogen functionalities into the surface was achieved via oxidation of the original carbon support followed by reduction with either urea or ammonia. SILP catalysts based on the so-obtained NDC materials provided higher activity in ethylene hydroformylation, while at the same time the formation of undesired aldol condensation products was low. Thus, the performance of the new SILP catalyst on NDC material represents a significant step ahead for a technically relevant, continuous catalytic operation with very high aldehyde selectivity.